Use of media as an indicator of modern trend of female Pakistani dakwah groups - Esma, Saima (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2015)
This study looked into the organized use of modern media technology by female Dakwah (Islamic propagation) groups in Pakistan as an indicator of modern trends prevalent among such groups. The two groups selected for this study were the Women’s Wing Jamaa’at e Islami and Al-Huda International Welfare Foundation. The time period of data is from June 2012 to December 2013. As a predominantly inductive research, this study shows that the ideological ground prepared by Women’s Wing Jama’at-e-Islami in Pakistani Muslim women was utilized by Al-Huda with a selective approach and a progressive use of modern media. It argues that a proactive discourse on status of women in Islam and female religious scholarship can be anticipated by such groups for being independent and pluralist. The study suggests a synergizing of likeminded groups towards women’s empowerment under the rubrics of Islam.